2014
DOI: 10.5586/am.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Noteworthy records of aphyllophoroid fungi in Finland (Basidiomycota)

Abstract: Aphyllophoroid fungi constitute an artificial order of fungi in Basidiomycota. It comprises a diverse group of different kind of fungi, such as corticioids, polypores and clavarioids. According to Kotiranta et al. [1] there are 980 aphyllophoroid species found in Finland. Aphyllophoroid fungi are important in decomposition of dead wood, and, thus they play an important role in woody ecosystems. In addition to wood decayers, a part of aphyllophoroid fungi are litter decayers, ectomycorrhizal, parasitic fungi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…(), Kunttu et al. (, , , ), and H. Kotiranta (update 2015, personal communication). Red‐listed species and the threat categories are awarded according to Kotiranta et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(), Kunttu et al. (, , , ), and H. Kotiranta (update 2015, personal communication). Red‐listed species and the threat categories are awarded according to Kotiranta et al.…”
Section: Methodsmentioning
confidence: 99%
“…and H.K). In this study, "rarely observed species" are considered having less than 10 earlier collections from Finland according to Kotiranta et al (2010), Kunttu et al (2011Kunttu et al ( , 2012Kunttu et al ( , 2013Kunttu et al ( , 2014, and H. Kotiranta (update 2015, personal communication). Red-listed species and the threat categories are awarded according to Kotiranta et al (2010).…”
Section: Study Design and Sampling Methodsmentioning
confidence: 99%
“…8 New to Southern Boreal, Lake District (2b), and Middle Boreal, Northern Carelia -Kainuu (3b). These are the third and fourth records of the species in Finland; previous records were from Salo (1b) and Lammi (2a) [2,8]. Endangered.…”
Section: Tulasnella Thelephorea 6thmentioning
confidence: 99%
“…), the majority of which are corticioids and polypores [2,4,5]. A large body of knowledge on the occurrence and distribution of aphyllophoroid species has been accumulated after the first Finnish checklist [2], especially on polypores and corticioids, but also on clavarioids (e.g., [3][4][5][6][7][8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-two species of Antrodia are known in Europe [3][4][5][6][7][8]. Among them, 15 species of Antrodia were described in Poland [9,10].…”
Section: Introductionmentioning
confidence: 99%